EVALUATION OF ANTIBACTERIAL RESISTANCE OF BIOFILM FORMS OF AVIAN SALMONELLA GALLINARUM TO FLUOROQUINOLONES - Kamashi, Kumar; Honnegowda, Mr.; Asha, Mayanna; Ms., Chandrakala (Universal Journal of Pharmaceutical Research, 2018)
Objective: Antimicrobial resistance is a growing concern worldwide. The indiscriminate use of antibiotics for a period of time has led to the emergence of antibiotic resistance in pathogenic bacteria. The present study was designed to evaluate the antibacterial efficacy of fluoroquinolone drugs, ciprofloxacin, enrofloxacin, moxifloxacin, sparfloxacin, norfloxacin, pefloxacin and ofloxacin against avian Salmonella gallinarum bacterial biofilms. Methods: The study parameters, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and biofilm elimination concentration (BEC) were determined on days 1, 3, 7, 10, 14 and 20 post inoculation for the planktonic (free) and biofilm cells of S. gallinarum by macro broth dilution method. The MIC and MBC values determined on days 1, 3, 7, 10, 14 and 20 for each of the fluoroquinolone drugs against the planktonic and biofilm forms of avian S. gallinarum were found to be non-significant. Results: BEC values determined against the biofilm forms of S. gallinarum during the study period were found to be non-significant among the tested fluoroquinolones. Conclusion: The results of the present study demonstrated that fluoroquinolone drugs were effective in vitro against both the planktonic and biofilm forms of avian S. gallinarum. Peer Review History: Received 6 June 2018; Revised 11 July; Accepted 23 September; Available online 15 September 2018 Academic Editor: Dr. Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Tamer Elhabibi , Suez Canal University, Egypt, tamer_hassan@pharm.suez.edu.eg Dr. Wilman Ismael Carrillo Terán , Technical University of Ambato Avda, Ecuador, wilmanct@gmail.com